1984
DOI: 10.1111/j.1476-5381.1984.tb16466.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P can contract the longitudinal muscle of the guinea‐pig small intestine by releasing intracellular calcium

Abstract: 1 The contraction of the longitudinal muscle of the guinea-pig isolated ileum in response to substance P (SP) in high [K+] 3 Bathing the ileum in a Ca2+-free medium for 2.5 min greatly diminished the potency and efficacy of SP in contracting the longitudinal muscle but concentrations of 2.2-22 tLM SP were still able to produce a response 30-40% of maximal. 4 The responsiveness to SP was completely lost within 10 min of bathing in Ca2+-free medium but was partially restored by a brief exposure (0.5 -2 min) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…In the control experiments, we employed substance P to induce the release of endogenous ACh from myenteric synaptosomes of guinea-pig ileum. Substance P works as an excitatory neurotransmitter in guinea-pig ileum (Franc0 et al 1979) via the release of ACh from myenteric plexus (Yau & Youther 1982) and the direct contraction of intestine (Holzer & Lippe 1984). Our results are in agreement with the previous view (Holzer & Lembeck 1980) that substance P induced the Cadependent release of ACh from myenteric plexus.…”
Section: Discussionsupporting
confidence: 92%
“…In the control experiments, we employed substance P to induce the release of endogenous ACh from myenteric synaptosomes of guinea-pig ileum. Substance P works as an excitatory neurotransmitter in guinea-pig ileum (Franc0 et al 1979) via the release of ACh from myenteric plexus (Yau & Youther 1982) and the direct contraction of intestine (Holzer & Lippe 1984). Our results are in agreement with the previous view (Holzer & Lembeck 1980) that substance P induced the Cadependent release of ACh from myenteric plexus.…”
Section: Discussionsupporting
confidence: 92%
“…In the control experiments, we confirmed that substance P induced a concentrationdependent release of endogenous ACh in guinea-pig ileum synaptosomes. Substance P works as an excitatory neurotransmitter in guinea-pig ileum (Franco, Costa & Furness, 1979) via the release of ACh from myenteric plexus (Yau & Youther, 1982) and/or the direct contradiction of intestine (Holzer & Lippe, 1984). Our results agree with the previous view (Holzer & Lembeck, 1980) that substance P induced the Cazf-dependent release of ACh from the myenteric plexus.…”
Section: Discussionsupporting
confidence: 91%
“…Many proteins observed in the previous study were correlated with the neurotransmission process, which is essential for the function of the GIT through ENS control. For example, the pattern of intestinal smooth muscle contraction can be modified when the release of neurotransmitters stimulating muscle contraction, such as SP 26 is increased or when the release of neurotransmitters promoting muscle relaxation, such as NO 27 , is decreased. In the present study, both conditions might have occurred, because we found a significance increase and decrease in the mean values of the SP varicosities area and the density of nNOS-IR neurons, respectively (Table 1 ), which is in accordance with our previous findings for the duodenum 13 .…”
Section: Discussionmentioning
confidence: 99%